Automating the generation of notifiable bacterial disease reports: proof-of-concept study and implementation in six hospitals in Thailand - Lim, C; Klaytong, P; Hantrakun, V; Rangsiwutisak, C; Phiancharoen, C; Tangwangvivat, R; Kripattanapong, S; Jitpeera, C; Poldech, W; Jiramahasan, P; Laosatiankit, B; Photivet, O; et al. (American Society of Tropical Medicine and Hygiene, 2024)
Information on notifiable bacterial diseases (NBD) in low- and middle-income countries (LMICs) is frequently incomplete. We developed the AutoMated tool for the Antimicrobial resistance Surveillance System plus (AMASSplus), which can support hospitals to analyze their microbiology and hospital data files automatically (in CSV or Excel format) and promptly generate antimicrobial resistance surveillance and NBD reports (in PDF and CSV formats). The NBD reports included the total number of cases and deaths after Brucella spp., Burkholderia pseudomallei, Corynebacterium diphtheriae, Neisseria gonorrhoeae, Neisseria meningitidis, nontyphoidal Salmonella spp., Salmonella enterica serovar Paratyphi, Salmonella enterica serovar Typhi, Shigella spp., Streptococcus suis, and Vibrio spp. infections. We tested the tool in six hospitals in Thailand in 2022. The total number of deaths identified by the AMASSplus was higher than those reported to the national notifiable disease surveillance system (NNDSS); particularly for B. pseudomallei infection (134 versus 2 deaths). This tool could support the NNDSS in LMICs.